ADVANTAGES AND LIMITS OF DUAL COMMITMENT IN FRENCH ORGANIZATIONS - Franck BIETRY; Sandra CAMUS; Mohamed-Zied AMARA (Revue de Gestion des Ressources Humaines, 2011)
Using a profile approach, the commitment scores of the employees simultaneously committed to their unions and their employing organizations (duallycommitted employees) are compared to those of unilaterally-committed employees. Our aim is to test some of the qualities attached to dual commitment. Two independent samples of employees working in private organizations, respectively consisting of 396 non-union employees and 1,100 union employees, are statistically analyzed. The results show that dual commitment attitude is found in French collective relationships, although traditionally considered as conflicting ones. Besides, they indicate among union employees that commitment scores both in organizations and unions are higher among duallycommitted than unilaterally-committed employees. Conversely, the results show no significant difference in organizational commitment when the sample of union employees is globally compared to that of non-union employees or when duallycommitted employees are compared to non-union, organizationally committed employees. The results encourage us to 1) revise the comparative studies about different collective relationship systems so as to better characterize them, 2) reassess the prerequisite role of social environment quality in dual commitment, and 3) qualify the positive effects of dual commitment